Plerixafor and granulocyte colony stimulating factor for poor mobilizers in patients undergoing autologous peripheral hematopoietic stem cell transplantation: Single institution study - El Cheikh, Jean; Terro, Khodr; El Warrak, Samantha; Ghaoui, Nohra; Sharrouf, Layal; Timonian, Michael Anthony; Ismail, Fatima; Zahreddine, Ammar; Kreidieh, Nabila; Moukalled, Nour; Abou Dalle, Iman; Bazarbachi, Ali (Frontiers in Transplantation, 2023)
Background: Autologous hematopoietic stem cell transplantation (ASCT) has become the mainstay treatment for many hematological malignancies and solid tumors. An adequate number of stem cells must be collected for better ASCT outcomes, which is challenging in 5-30% of patients. To improve mobilization, plerixafor is used along with granulocyte colony-stimulating factor (G-CSF). Patients and methods: We conducted a retrospective single center study involving patients who received plerixafor pre-ASCTs between January 2013 and December 2020 at a tertiary care center in Lebanon. We identified a total of 84 consecutive adult patients. All patients identified were poor mobilizers and have eventually received plerixafor either as pre-emptive use before first apheresis in those with peripheral CD34+ of less than 20 cells/ul, or after failure of first apheresis in those with peripheral stem cells (PSC) >2.0 x106 cells/Kg. Results: The median age at ASCT was 52.7 years (22-74) with 61% male predominance. Multiple myeloma was the most prevalent disease 64% followed by Lymphoma 32%. The majority of patients were in complete remission 64% at the time of ASCT. Most patients received proteasome inhibitor-based induction therapy 67% and Melphalan-based conditioning therapy 68%. The median follow-up from ASCT was 9 months (1-59). It was noted that greater body mass index (BMI) is a significant factor for better PSC collection whether premobilization (P=0.003), or post plerixafor mobilization (P=0.024). Moreover, Multiple Myeloma patients showed better mobilization using Plerixafor (P=0.049). Using Plerixafor along with G-CSF in poor mobilizers post G-CSF alone showed a statistically significant increase in the collected PSC mean from 0.67 x106 cells/Kg to 4.90 x106 cells/Kg (P< 0.001) with a failure rate only for 12 patients (15%). The infusion of PSC > 2.5x106cells/Kg has shown 3 days decrease in time to platelet engraftment (P=0.021) and a 36% decrease in progression/relapse rate (P=0.025). Conclusion: Plerixafor is effective in increasing the PSC yield in poor mobilizers. Low BMI and hematologic malignancies other than Multiple Myeloma are risk factors for poor mobilization. More studies should be performed to establish more risk factors, helping us to identify poor mobilizers more accurately and initiate plerixafor mobilization early on.